2021
DOI: 10.1016/j.heliyon.2021.e05993
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable removal of anodized aluminum dye by groundwater treatment waste: experimental and modeling

Abstract: Groundwater treatment waste (GWTW), as an environmentally friendly renewable nanomaterial, was implemented for the removal of anodized aluminum dye Sanodure Green (SG) from aqueous solutions. The capability of the SG metal complex dye removal was assessed by measuring solution decoloration and chromium elimination degree. GWTW was characterized using FTIR, SEM, EDX, TEM, XPS and surface area measurements. Kinetic curves were obtained by changing initial dye concentration, pH, temperature and adsorbent dose. Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…At the same time, it has been found that the rate of adsorption ( k 2 ) decreases with the increasing concentration of adsorbate NDPhA which might be attributed to a repulsion between the molecules in the bulk as well as at the adsorbent surface. Similarly, R 2 values obtained from the Elovich model are also high which indicates the mechanism of the heterogeneous diffusion process 57 …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…At the same time, it has been found that the rate of adsorption ( k 2 ) decreases with the increasing concentration of adsorbate NDPhA which might be attributed to a repulsion between the molecules in the bulk as well as at the adsorbent surface. Similarly, R 2 values obtained from the Elovich model are also high which indicates the mechanism of the heterogeneous diffusion process 57 …”
Section: Resultsmentioning
confidence: 73%
“…Freundlich n 1.56 Similarly, R 2 values obtained from the Elovich model are also high which indicates the mechanism of the heterogeneous diffusion process. 57 For further investigation, the diffusion mechanism of the NDPhA molecules was examined, and the resistance of mass transfer on the binding of NDPhA on the surface of SG was investigated by fitting the equilibrium adsorption data with the most widely used intraparticle diffusion model described by Weber and Morris. 52 In general, in a well-designed adsorption experiment, the adsorption process occurs in three consecutive stages; (i) diffusion of particle through the boundary layer, which is also known as film diffusion, (ii) intra-particle diffusion of adsorbate through the interior pores of the adsorbent, and (iii) adsorption of adsorbate molecules onto the active sites on the interior surface of the adsorbent.…”
Section: Parameter Valuementioning
confidence: 99%
“…The adsorption capacity and catalytic activity are strongly related to the specific surface area of iron-oxide minerals (Garrido-Ramírez et al, 2010). The BET-specific surface area of raw GWTW dried at room temperature and used in this work for the SG dye adsorption and destruction was 34.76 m 2 g -1 (Sodaitienė et al, 2021).…”
Section: Characterization Of the Gwtwmentioning
confidence: 99%
“…Owing to the increasing demand for environmental protection, several conventional treatment methods have been reported by researchers to effectively remove pollutants from wastewater. For instance, ion exchange [ 10 ], reverse osmosis [ 11 ], nanofiltration [ 12 ], biological technique [ 13 ], coagulation/flocculation [ 14 ], reverse osmosis [ 15 ], chemical precipitation [ 16 ], photocatalysis [ 17 , 18 ], membrane processes [ 19 ], advanced oxidation processes [ 8 ] and adsorption process [ 20 ]. However, some of the highlighted methods have their limitations that are either require frequent maintenance, high cost of operation, longer degradation time, generation of sludge in large amounts and the use of expensive chemicals [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%